Manipulation of combustion waves in carbon-nanotube/fuel composites by highly reactive Mg nanoparticles. Issue 40 (30th September 2015) - Lee, Kang Yeol; Hwang, Hayoung; Shin, Dongjoon; Choi, Wonjoon
Abstract : Highly reactive Mg/MgO nanoparticles enable the amplification of chemical combustion in a hybrid composite of carbon nanotubes and chemical fuel. Abstract : Manipulating the interface of micro/nanostructured materials and chemical fuels can change the fundamental characteristics of combustion waves that are generated during a reaction. In this study, we report that Mg/MgO nanoparticles actively amplify the propagation of combustion waves at the interface of multi-walled carbon nanotubes (MWCNTs) and chemical fuels. Fuel/MWCNT and fuel/MWCNT–Mg/MgO composite films were prepared by a facile synthetic method. We present complete physiochemical characterization of these composite films and evaluate the propagating velocities and real-time surface temperatures of combustion waves. Mg/MgO nanoparticles at the interface enhanced the reaction front velocity by 41%. The resulting explosive reactions supplied additional thermal energy to the chemical fuel, accelerating flame propagation. Furthermore, the surface temperatures of the composites with Mg/MgO nanoparticles were much lower, indicating how the transient heat from the reaction would ignite the unreacted fuels at lower surface temperatures despite not reaching the necessary activation energy for a chain reaction. This mechanism contributed to thermopower waves that amplified the output voltage. Furthermore, large temperature gradients due to the presence of nanoparticles increased charge transport inside the nanostructured material, due to the increased thermoelectric effects. This manipulation could contribute to the active control of interfacially driven combustion waves along nanostructured materials, yielding many potential applications.